Analisis Kesiapan Guru dalam Pelaksanaan Pembelajaran Coding melalui Metode Gamifikasi di MIN 1 Dairi - aritonang, elsida; Hutauruk, Deswidya Sukrisna; Harefa, Syukur Bestin; Sari, Wulan Yulita (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2025)
Teachers are an important component of the education system that prioritizes the development of fundamental digital skills. Recognizing the importance of coding skills because they train the mindset to find and solve problems creatively, even in children aged 4-5 years, developed countries have included these skills in the school curriculum from an early age. Gamification encourages students to be more active and enthusiastic when participating in class, so that to equip students with 21st-century skills and direct students to behave positively, the researcher is interested in seeing the readiness of teachers in welcoming and implementing coding learning using the gamification method at MIN 1 Dairi. The problem formulation of this study is how Teacher Readiness in Implementing Coding Learning with the Gamification Method at MIN 1 Dairi. This study aims to describe the readiness of teachers in Implementing Coding Learning with the Gamification Method at MIN 1 Dairi. The research concluded that the planning and implementation of teacher readiness for coding learning at MIN 1 Dairi encompassed the learning foundation, objectives, approaches, models, media, introductory, core, and closing activities, assessment, and management. This demonstrates that teachers are sufficiently prepared to teach coding to all students at MIN 1 Dairi, despite the need for improvement in facilities and infrastructure